2014
DOI: 10.1371/journal.pntd.0003337
|View full text |Cite
|
Sign up to set email alerts
|

Global Metabolomic Profiling of Acute Myocarditis Caused by Trypanosoma cruzi Infection

Abstract: Chagas disease is caused by Trypanosoma cruzi infection, being cardiomyopathy the more frequent manifestation. New chemotherapeutic drugs are needed but there are no good biomarkers for monitoring treatment efficacy. There is growing evidence linking immune response and metabolism in inflammatory processes and specifically in Chagas disease. Thus, some metabolites are able to enhance and/or inhibit the immune response. Metabolite levels found in the host during an ongoing infection could provide valuable infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 60 publications
(70 reference statements)
7
70
0
Order By: Relevance
“…Plasma uric acid was decreased in males with CFS (Table 2, Males). Uric acid is the end product of purine metabolism and an important antioxidant molecule (14,15). Plasma adenosine was decreased in females (Table 3, Females).…”
Section: Control Controlmentioning
confidence: 99%
“…Plasma uric acid was decreased in males with CFS (Table 2, Males). Uric acid is the end product of purine metabolism and an important antioxidant molecule (14,15). Plasma adenosine was decreased in females (Table 3, Females).…”
Section: Control Controlmentioning
confidence: 99%
“…Diets regulate the immunometabolic status of the host, which influences the severity of the disease, and thus, the serum metabolic profiling differs between different pathological conditions. Changes in host metabolomic profiling were demonstrated during acute stages of infection in a murine model of T. cruzi infection [19]; however, those observations cannot be extrapolated to evaluate the metabolic changes during the chronic stage of infection (occurring after several weeks in the murine model and after years/decades of infection in human disease), and the disease pathways are different between the acute and the chronic stage of infection. The current study analyzed the serum metabolomic profile of T. cruzi-infected mice fed on different diets that specifically developed RV and LV dilations.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the global metabolomic profiling during the acute stage of T. cruzi infection in a murine model have been demonstrated [19]. However, the metabolomic profiles differ between acute and chronic stages of Chagas disease, and the progression to CCM is associated with the chronic phase of infection.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mass spectrometry (MS) methods provide a robust, versatile and sensitive analytical technology allowing high-throughput detection with mass accuracy, precise quantitation and verification of protein variants, splice isoforms, metabolites and disease-specific post-translational modifications (Crutchfield et al, 2016). Indeed, using MS-based approaches, global changes in metabolic profiles in Chagasic patients showing acute myocarditis (Girones et al, 2014) and serological biomarkers showing differences between Chagasic and healthy subjects (Santamaria et al, 2014) were recently identified. In the latter case, biomarker peaks with the best discriminatory power were further characterized by a range of proteomic and immunological techniques, indicating that specific fragments derived from proteolysis of apolipoprotein A-I and one fragment of fibronectin are specifically upregulated in Chagasic patients (Santamaria et al, 2014).…”
Section: Diagnostic Applications For Chagas D Isease: the Road Aheadmentioning
confidence: 99%